Fenomena Jariyah Khalifah Daulah Abbasiyah tahun 170 H - 247 H / 786 - 861 M. - Haukil Haukil (Program Studi Sejarah Peradaban Islam Fakultas Adab dan Humaniora UIN Sunan Ampel Surabaya, 2017)
Thelarge number of jÄriyah owned by the caliphs of Islam ever became phenomenal in the early period (170 H / 786 M-247 H / 861 AD) of Abbasid rule. Thisstudy aims to determine the factors boosting the phenomenon of jÄriyah ownership in large number by the caliphs of the Abbasid rulein the early period. In addition, this study also wants to know the purpose of the caliphs in owning jÄriyah in large number. This study is a historical research using literature referring to written sources, such as books dealing with the early period of the Abbasid rule, especially the books that deal with the phenomenon of jÄriyah ownership in large number. Through historical and sociological approach, with functional-structuralism as a framework, the results of this study indicate that the large number of jÄriyah owned by the caliphs of the Abbasid in the early period has a very close relationship with the progress (economic, social, political) achieved by the Abbasid at that time; the legitimacy of the practice of slavery in Islam, the expansion of region (futÅ«hÄt), the advance of economic trade-sectors, the advance of entertainment in society, and the influence of Ctesiphon. In addition, jÄriyah ownership in large number did not show high sexual desire of the caliphs, but it was only as ymbol of power, as indicated by: it was only people with power who typically have jÄriyah in large quantities; strong tradition of gift-reward slaves; and not all jÄriyahs laid by their masters (sayyid).